Når retten sætter pris på krænkelse - Et sociologisk studie af tortgodtgørelse i danske voldtægtssager - Stubkjær Nissen,Andrea (2026)
This thesis examines how rape is assessed and valued in Danish court practices concerning compensating rape victims for non-economic damage, and how these assessments can be understood from a socio-legal and feminist perspective. The thesis investigates, what factors are considered significant in the determination of compensation in rape cases, and how these assessments can be understood in relation to perceptions of rape, gender, sexual autonomy, and legal objectivity. The study is based on a qualitative analysis of 13 Danish rape judgments and six interviews with victim lawyers. The analysis draws on socio-legal and feminist legal theoretical perspectives, including the work of Carol Smart, Susan Estrich, Martha Burt, and Nils Christie. The analysis indicates that compensation for rape is closely linked to factors such as physical violence and active resistance, as these circumstances results in higher levels of compensation. In contrast, cases characterized by passivity and lack of resistance are typically awarded significantly lower compensation. The thesis further demonstrates how these assessments may be linked to broader societal conceptions of what constitutes a “real rape” and the “ideal victim”. Furthermore, the thesis argues that the court assessments are presented as objective and standardized, even though they simultaneously rely on normative and socially situated understandings of rape and violation. The thesis therefore argues that compensation practices contribute to a hierarchization of different forms of rape and violation.
Keywords: Rape; victim; compensation; socio-legal studies